Predicting global crisis recovery period: lesson from 1997 crisis - Duasa, Jarita; Ahmad, Nursilah (Taylor & Francis Group, 2010)
The objective of this paper is to identify the best indicator in forecasting the recovery period from the current global crisis for Malaysia. Initially, to determine the best indicator for the recovery period, we construct a simple forecasting model that incorporates three indicators: lagging, leading and coincidence indices, with two proxies of economic performance, macroeconomic and financial variables. We estimate a two-variable VECM model using monthly and quarterly data covering the period 1980 to 2000. We alternate between the three indicators and we evaluate each model using out-of-sample forecast. Using the results of the initial process of analysis, we predict the recovery period of Malaysian economy from the current global economic crisis. It is found that lagging index is the best indicator of financial performance of the economy. From the half-life calculation base on error correction term, the study found that Malaysia was able to recover from the previous 1997 crisis within two to four years period after the crisis. Given that the current crisis environment is similar to the previous 1997 crisis, similar time period could applied to the current global crisis recovery.